Analisis Optimasi Opersasi Waduk Ir. H. Djuanda Jatiluhur Untuk Pembangkitan Listrik dengan Menggunakan Solver - Prasetyo, Firman Agung; , Gurawan Djati Wibowo, ST. M.Eng; , Ir. Achmad Karim Fatchan,M.T (2017)
Dam is a water reservoir used to store water when there is excess water in the rainy season, and is used to serve the needs of water. By applying the principle of optimization of reservoir operation, expected potential of water resources can be used optimally to meet human needs. Based on the function, the reservoir is classified into two, namely, reservoirs single-purpose, the reservoir is used for only one purpose, as well as multi-purpose reservoirs, the reservoir is used for various purposes. This study aimed to evaluate the operating pattern Ir. H. Juanda Jatiluhur in generating electricity, applying the principle of optimization solver, so the results obtained maximum power generation. Solver is an enhancement (add-in) that is used to solve the problems contained in the application program Microsoft Excel. In other words, the Solver can handle problems involving many variables cells and to help find a combination of variables to minimize or maximize the value of the target cell. Solver allows to define itself a restriction or obstacle that must be met in order to correct the perceived problem solving. Ir. H Juanda Jatiluhur, indicating the potential inflow volume 80% Ir. H Juanda's Jatiluhur largest, amounting to 4,373,846,208.00 m3/year. The results of the optimization solver calculation shows that the calculation results of the electric energy generation by using the optimization solver is greater than the realization of the existing power generation by a margin of 20.87%.